Hardware development of 2D force feedback device for virtual reality in medicine - Ba Waqash, A.; Sati, M.; Kostin, D. O.; Tymkovych, M. Y. (Харків, ХНУРЕ, 2019)
The development of haptic devices for surgery is an important task. The importance of constructing force-feedback haptic devices for modern medicine is shown. In these theses, a block diagram of such the device is proposed. The next steps are to develop the force feedback device.
Keywords: haptic device; force-feedback; block diagram